Vaccine prevention of meningococcal disease in Africa: Major advances, remaining challenges - Mustapha M. Mustapha; Lee H. Harrison (Taylor & Francis Group, 2018)
Africa historically has had the highest incidence of meningococcal disease with high endemic rates and periodic epidemics. The meningitis belt, a region of sub-Saharan Africa extending from Senegal to Ethiopia, has experienced large, devastating epidemics. However, dramatic shifts in the epidemiology of meningococcal disease have occurred recently. For instance, meningococcal capsular group A (NmA) epidemics in the meningitis belt have essentially been eliminated by use of conjugate vaccine. However, NmW epidemics have emerged and spread across the continent since 2000; NmX epidemics have occurred sporadically, and NmC recently emerged in Nigeria and Niger. Outside the meningitis belt, NmB predominates in North Africa, while NmW followed by NmB predominate in South Africa. Improved surveillance is necessary to address the challenges of this changing epidemiologic picture. A low-cost, multivalent conjugate vaccine covering NmA and the emergent and prevalent meningococcal capsular groups C, W, and X in the meningitis belt is a pressing need.